2018
DOI: 10.1007/s10508-018-1217-4
|View full text |Cite
|
Sign up to set email alerts
|

ERPs Reveal Disengagement Processes Related to Condom Use Embarrassment in Intention-Behavior Inconsistent Young Adults

Abstract: The use of barrier protections such as condoms has consistently been reported to reduce the acquisition of sexually transmitted infections. However, it has also been reported that the association between condom use intentions and behavior is, at best, often weak. Furthermore, embarrassment associated with purchasing condoms and negotiating their use has been shown to negatively impact the frequency of condom use. Using electroencephalography to analyze P300 event-related potential components known to measure e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…11 One of the most important ways to prevent the transmission of HIV in sexual relationships is the use of condoms. [12][13][14][15] However, there is much resistance to not using it, 16 with a prevalence of 0.42% reported among female sex workers. 4 Lack of condom use is affected by various personal, social, environmental, and cultural factors.…”
Section: Introductionmentioning
confidence: 99%
“…11 One of the most important ways to prevent the transmission of HIV in sexual relationships is the use of condoms. [12][13][14][15] However, there is much resistance to not using it, 16 with a prevalence of 0.42% reported among female sex workers. 4 Lack of condom use is affected by various personal, social, environmental, and cultural factors.…”
Section: Introductionmentioning
confidence: 99%
“…Along with identifying the types of marketing stimuli which evoke greater attentional responses, ERPs may provide insights to pressing consumer and marketing issues, such as the intention-behaviour gap (see Lim and Weissmann (2021) for review). For example, individuals who are high in intention for condom use but low in their actual condom use (intention-behaviour gap) show a reduced P300 amplitude to relevant health information in comparison to individuals who are intention-behaviour consistent (Brüll et al, 2019). This was suggested to indicate that individuals with an intention-behaviour gap are likely to disengage attentional processes to this health information.…”
Section: The Application Of Electroencephalography and Event-related ...mentioning
confidence: 99%
“…The second column in Table 1 presents the outcomes of the review on the evidence supporting the results of the brainstorm. The intervention planners identified empirical evidence for some issues related to unprotected sex that were not already brainstormed, for example not perceiving condoms as a means of pregnancy prevention ( 28 ) or perceiving condoms as embarrassing ( 29 , 30 ). The planning group also identified a number of studies that reported the relationship between unsafe sex and various theoretical constructs (listed in the third column): intention to use condoms and perceived norms ( 28 , 31 ) and self-efficacy in terms of negotiating and discussing condom use with partners ( 29 , 32 ).…”
Section: Example: Applying Core Processesmentioning
confidence: 99%